Differentiation of Rheumatoid Arthritis From HCV Infection: Rheumatoid Factor, Anti-Cyclic Citrullinated Peptide or Anti-Mutated Citrullinated Vimentin? - Ece Kaptanoğlu,; Işılay Nadir,; Zahir Bakıcı,; Emrullah Hayta,; Mehmet Türkmen,; Hafize Sezer,; Sami Hizmetli,; Hasan Elden, (Archives of Rheumatology, 2010)
Objective: Differentiation of rheumatoid arthritis (RA) from other diseases with joint involvement such as hepatitis-C virus (HCV) infection represents a diagnostic problem. In addition to the rheumatoid factor (RF), more specific and sensitive auto-antibodies are under evaluation in recent years with conflicting results. In this study, we tested the diagnostic value of rheumatoid factor, anti-cyclic citrullinated peptide (anti-CCP) and anti-mutated citrullinated vimentin (anti-MCV) in distinguishing RA from hepatitis C patients. Materials and Methods: Sera of 34 RA patients and 30 hepatitis C patients were tested for RF, anti-CCP anti-MCV. Disease activity was determined by disease activity score (DAS-28) 28 in RA and by modified Knodell score in hepatitis C patients. Extra-articular involvement in RA and rheumatologic involvement in hepatitis C patients were documented. Results: In roc analysis, area under curve (AUC) was the highest in anti-CCP. Sensitivity and specificity was 82% and 53%, 79%, and 96% and 70%, and 73% for RF, anti-CCP and anti-MCV respectively. DAS-28 has a weak correlation with RF (r=0.406), anti-CCP (r=0.433), and anti-MCV (r=0.453). There was no difference between the patients in autoantibody levels regarding extra-articular involvement and DAS-28 in RA, and joint involvement in hepatitis C patients. Conclusion: Anti-MCV antibodies may be useful in distinguishing RA however it seems to have no additional value over anti-CCP or RF in hepatitis C patients. Anti-CCP antibodies are more reliable in diagnosis of RA due to their high specificity. (Turk J Rheumatol 2010; 25: 19-23)